Berührungslose Formgebung mit Laserstrahlung - Holzer, Stefan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1996)
Depending on the parameters laser forming shows three different mechanisms, which allow concave and convex bendings and in-plane contraction. The development of suitable FEM models and a systematic experimental validation improved the knowledge about this process especially by the calculation of quantities, which cannot be acquired by experiments. The temperature-gradient-mechanism (TGM) uses the temperature difference between the irradiated and the non-irradiated surface in order to obtain a concave bending, which is defined by a movement of one bending leg towards the heat source. For high-precision bending with the TGM a closed-loop was designed. Several control strategies were discussed, which allow in principle any desired accuracy. A totally different mechanism is working if the irradiation time increases and the temperature gradient lowers. If the diameter of the heated area is big compared to the sheet thickness, the thermal stresses may cause buckling. This buckling mechanism allows convex bendings. The third mechanism is activated also by a homogenous heating of the total sheet thickness. If the diameter of the heated area is too small in order to cause buckling, the thermal stresses will cause an in-plane contraction. Analytical and numerical calculation models for these effects meet the basic requirements for a successful usage of laser forming for accurate alignment and rapid-prototypin